Phonological Errors in Balinese Language Reading Among Children with Intellectual Disabilities: An Analytical Study - Putu Aditya Antara; Komang Ayu Dipla Denia; Made Vina Arie Paramita (Thinking Skills and Creativity Journal, 2024)
Children with special needs often face difficulties in reading, including frequent errors in word pronunciation, particularly in the Balinese language. This study aims to analyze the phonological errors in reading and understanding Balinese among children with intellectual disabilities. The subjects of this study consist of two classes, with a total of 15 students. The data collection methods and instruments used include observation sheets, interviews, and documentation. The data analysis technique employed is qualitative descriptive analysis, while data validity is ensured through triangulation, which consists of data collection, data reduction, data presentation, and conclusion drawing. The findings of this study indicate the presence of phonological errors, such as mispronunciations involving phoneme omission and phoneme addition in Balinese language sounds. It can be concluded that the factors contributing to these phonological errors include low cognitive ability, students' tendency to become easily bored or struggle with learning comprehension, and the influence of their first language or surrounding environment. The implications of this study are expected to serve as a reference for teachers in inclusive schools to improve Balinese language instruction for students with special needs.